Ambidexterity Strategy, Digital Innovation for Street Vendor Sustainability in the Creative Economy Era - Mohamad Yamin; Nino Nopriandi Saleh; Inna Mukhaira (Universitas Negeri Gorontalo, 2026)
Purpose: This research aims to identify an effective strategy for sustaining street vendor entrepreneurship in Tangerang City, particularly by integrating ambidexterity and digital innovation with approaches to economic, technological, organizational, and environmental factors relevant to the challenges entrepreneurs often face.Design/Methodology/Approach: In this research, researchers tested models and hypotheses using the PLS technique. PLS (Partial Least Squares) analysis consists of two parts: outer model and inner model evaluation. Using a survey or questionnaire with 200 respondents, street vendors in Cipondoh District, Tangerang City. Data was collected for 13 days. Data was collected using purposive sampling.Findings: The research results show that the Ambidexterity Strategy and Digital Innovation play significant roles for the Street Vendor Sustainability Business in Cipondoh, Tangerang. Economic, Environmental, and technological factors significantly affect the Ambidexterity Strategy. In contrast, Organizational Factors have an impact but do not significantly impact the Ambidexterity Strategy for Street Vendors in Cipondoh, Tangerang.